Technological Inclusion in Times of Pandemic: A Review of Constructivism as a Theoretical Foundation (Docentes 2.0 Journal, 2022)
The COVID-19 pandemic expanded the usage of technological resources globally. In the educational field, technological resources and tools became the only instruments of mediation between teachers and students. This desk research was based on the hermeneutical paradigm from a narrative-interpretative qualitative approach. A bibliographic design was applied. The study's objective was to analyze the constructivist theory as a theoretical basis for designing technology-supported learning experiences. The results demonstrated that although technology facilitates the implementation of teaching based on constructivism, access to technological resources becomes a limitation. Considering that including technology in educational processes does not constitute a determining factor of effectiveness, reflecting on a theoretical foundation that strengthens the teaching position regarding technological inclusion is necessary.
Keywords: Technological inclusion; pandemic; constructivism, technology